2020
DOI: 10.1155/2020/9867693
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Fast Recovery from Idiopathic Facial Paralysis Using Laser-Photobiomodulation

Abstract: Idiopathic facial paralysis, also known as Bell’s palsy, exerts a negative effect on the quality of life. Although the prognosis is good in the majority of cases, a significant percentage of affected individuals may have sequelae that can negatively affect their lives. The use of therapeutic measures as early as possible can improve the prognosis. This article describes the successful use of laser-photobiomodulation as a single therapy in a patient with Bell’s palsy and confirms the possibility of using this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
0
17
0
2
Order By: Relevance
“…[17][18][19] Of 8 human studies, 2 studies were designed as randomized controlled study (RCT) 21,22 and 6 studies were descriptive studies (Table 2). [23][24][25][26][27][28] One study had two parallel RCT design, the LLLT group and control group. 21 The other study had three parallel RCT design including highlevel laser therapy, LLLT group, and control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Of 8 human studies, 2 studies were designed as randomized controlled study (RCT) 21,22 and 6 studies were descriptive studies (Table 2). [23][24][25][26][27][28] One study had two parallel RCT design, the LLLT group and control group. 21 The other study had three parallel RCT design including highlevel laser therapy, LLLT group, and control group.…”
Section: Resultsmentioning
confidence: 99%
“…Of 6 descriptive studies, one study was clinical intervention study on effect of LLLT in diabetics with bell's palsy 23 and 5 articles were case report. [24][25][26][27][28] These descriptive studies applied NIR range of wavelength with various number of treatment session and period of treatment ( Table 2). All researchers in the descriptive studies reported improvement of Bell's palsy on House-Brackman (H-B) grade following LLLT at the ending of their treatment sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, PBM was proposed as an approach in the treatment of BP [17]. Tanganelli et al [39], on a single patient, concluded that a single session of PBM therapy was an effective option for those affected by BP. Kumar [40] concluded, in a study on five patients, that class IV level laser therapy can support the medical management of BP, including cases with adverse effects from corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…In their case study, Tanganeli et al [12] examined the outcome of low-power laser therapy in one patient. The patient was 71 years old diagnosed with grade V (severe) Bell's palsy, according to the HBS.…”
Section: Literature Reviewmentioning
confidence: 99%